2021
DOI: 10.1097/sap.0000000000002702
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Distraction Osteogenesis as a Primary Intervention in Infants With Pierre Robin Sequence

Abstract: Background Pierre Robin sequence (PRS) is a triad of congenital facial abnormalities that can present as a syndrome (syndromic PRS [sPRS]) or an isolated entity (isolated PRS [iPRS]). Patients with PRS can develop airway and feeding problems that may result in failure to thrive. Mandibular distraction osteogenesis (MDO) is a method for improving the functional issues associated with breathing and feeding. There is a Paucity of literature evaluating the outcomes of MDO between sPRS and iPRS patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…36 Mandibular distraction has been the gold standard for the management of OSA in children with Pierre Robin sequence, secondary to the underlying retrognathia as the primary cause of obstruction. 37 Although preliminary results of hypoglossal nerve stimulation show promise in the pediatric population, it is still not FDA-approved for use in children and its scope of application is only targeting children with Trisomy 21 and severe OSA above ten years old. 19 TBS is an alternative intervention that has been uncommonly described in children with OSA and glossoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…36 Mandibular distraction has been the gold standard for the management of OSA in children with Pierre Robin sequence, secondary to the underlying retrognathia as the primary cause of obstruction. 37 Although preliminary results of hypoglossal nerve stimulation show promise in the pediatric population, it is still not FDA-approved for use in children and its scope of application is only targeting children with Trisomy 21 and severe OSA above ten years old. 19 TBS is an alternative intervention that has been uncommonly described in children with OSA and glossoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…McCarthy et al ( 12 ) firstly reported gradual mandibular elongation in cases with congenital hypoplasia in 1992. Later on, prospective research of Soto et al ( 13 ) evaluated 29 cases with tongue-based upper airway obstruction treated with mandibular DO. Decannulation or extubation was performed postoperatively in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The study on the nutritional status mainly focused on the changes in weight and body length followed by the airway improvement. More people believed that the improvement of nutritional status is a result of the alleviation of airway problems (24)(25)(26). However, some scholars believe that nutritional changes should be studied independently with airway changes, because breathing and swallowing difficulties in PRS patients may not only be related to anatomical variation (such as micrognathia and glossoptosis etc.…”
Section: Discussionmentioning
confidence: 99%